2005
DOI: 10.1007/s00381-005-1235-0
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric neurotrauma in Kathmandu, Nepal: implications for injury management and control

Abstract: Four hundred sixteen injured children were admitted to hospital, and the charts for 352 (85%) were available for review. Spinal injuries were relatively rare (4%) compared to head injuries (96%). Falls were the most common cause of injuries (61%). It took significantly longer (p<0.001) for children injured in rural Nepal (62%) to obtain neurosurgical care (30.1 h) than those injured within Kathmandu (7.1 h). A Glasgow Outcome Score of 5 was obtained for 96%, 76%, and 22% of patients with mild, moderate, or sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…A study from Nepal found that patients in rural areas took on average 30 h longer to obtain definitive neurosurgical care than their urban counterparts [11]. While the present study could not examine these differences, the limited availability of emergency medical facilities in rural Fiji mean these differences are also likely to exist in Fiji.…”
Section: Discussionmentioning
confidence: 73%
“…A study from Nepal found that patients in rural areas took on average 30 h longer to obtain definitive neurosurgical care than their urban counterparts [11]. While the present study could not examine these differences, the limited availability of emergency medical facilities in rural Fiji mean these differences are also likely to exist in Fiji.…”
Section: Discussionmentioning
confidence: 73%
“…32,69,70 In contrast, Map 2 also demonstrates a high proportion of paraplegia secondary to high falls in Asia, South (Pakistan, Bangladesh and Nepal) as well as a component of low falls (Bangladesh). [71][72][73] Violence-related TSCI occurs in regions of conflict or high availability of weapons (gunshot wounds and stabbings). 7,46,74 The Maps reveal a band of violence through North and South America into Southern Africa and the Middle East.…”
Section: Discussionmentioning
confidence: 99%
“…In developing countries, low falls resulting in TSCI occur while carrying heavy loads on head in young people. 73,80 TSCI due to crush factors from collapse of ceiling in poorly regulated mining activities is common in many developing countries. 79 Diving into water of unknown depths results in high proportions of tetraplegia in rivers and coastal regions.…”
Section: Discussionmentioning
confidence: 99%
“…26 Data from Bangladesh also had high number of falls (63%), out of which 43% of the falls involved falls from trees and 20% while carrying heavy loads. 27 Mukhida 28 provided statistics for people in Nepal under the age of 19, in which 61% of SCI was due to falls (mainly from rooftops as opposed to trees in the rest of the region). Incidence data are inadequate for this region.…”
Section: Asia Southmentioning
confidence: 99%